Updated meta-analysis of controlled observational studies: proton-pump inhibitors and risk of Clostridium difficile infection. Issue 1 (January 2018) - Cao, F.; Chen, C.X.; Wang, M.; Liao, H.R.; Wang, M.X.; Hua, S.Z.; Huang, B.; Xiong, Y.; Zhang, J.Y.; Xu, Y.L.
Summary: Attention has recently been directed toward a plausible link between Clostridium difficile infection (CDI) and proton-pump inhibitors (PPIs). However, the results of studies on the association between CDI and PPI remain controversial. We searched the literature databases from their inception to December 2016, without restriction of language, including all controlled observational studies examining the association between acid-suppressive therapy and CDI. Pooled analysis of 50 studies showed a significant association between PPI use and risk of developing CDI (odds ratio: 1.26; 95% confidence interval: 1.12–1.39) as compared with non-users. When stratified by study patients, the relative risk of hospital-acquired CDI and community-associated CDI were 1.29 (1.14–1.44) and 1.17 (0.74–1.59). After restricting the studies according to hospital department, the relative risks of hospital-acquired CDI in ICUs and general wards were 1.43 (0.74–2.11) and 1.29 (1.13–1.45). By implementing cumulative meta-analysis, it was clear that earlier trials of CDI conducted in the early 2000s demonstrated a high degree of heterogeneity and a high percentage of negative results. Since 2011, the overall association between PPI use and risk of developing CDI has remained relatively stable within an effect size between OR 1.20 and 1.26. Our findings indicate a significant associated risk of incident CDI among PPI users, especially in general ward patients. The totality of evidence, when using cumulative meta-analysis, showed that further trials are unlikely to overturn this positive result. Therefore establishing a guideline for the use of PPIs may help in future with the control of CDI.